The Analisis Faktor Penghambat Rendahnya Literasi Numerasi Siswa Kelas V SDN 3 Jinengdalem - Ina, Komang Ina Sekarini; Saharani, Komang Putri; Darma, Ketut Ari Sukra; Marheni, Kadek Rizka; Prasista, Komang Dina; Werang, Basilius Redan (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
The implementation of numeracy literacy at SD N 3 Jineng Dalem, Buleleng is still relatively low. The ANBK results and report card scores show that numeracy literacy is still at a low level or lacking. This research aims to describe the results of a study regarding factors inhibiting low numeracy literacy in terms of the learning outcomes of grade 5 students at SD 3 Jineng Dalem. The methods used in this research are qualitative research, field studies using observations and interviews, as well as literature studies by reviewing several relevant articles. The results of this research are as follows a). Numeracy literacy skills at SD N 3 Jineng Dalem are classified as low/deficient due to several factors. b). Factors include lack of learning media, low student motivation to learn, low student learning ethos, and lack of parental support. So from these factors the solution that can be given to overcome these factors is a comprehensive and collaborative approach, utilizing digital resources, giving awards, providing feedback, and building communication.